Scale-up and biomass hold-up characteristics of biological fluidized bed reactors - Idris, A. H.; Turan, M.; Ozturk, I. (IWA Publishing, 1994)
This paper presents a comprehensive study results on scale-up and biomass hold-up characteristics of biological fluidized bed reactors (BFBR). The overall objective of this study was to establish and test some basic design criteria for the scaling-up or scaling-down of anaerobic fluidized bed reactors. A 12.5 1 laboratory-scale fluidized bed was designed and constructed based on a geometrically similar 70 1 pilot scale fluidized bed and the process performances were compared. Biomass hold up characteristics of the BFBRs were also investigated during the experimental studies. A general expression was developed for predicting the biological fludized bed porosities. Using this expression, both the local and overall fluidized bed porosities could be predicted depending on biofilm thickness, expansion coefficient, media diameter and density. The validity of this expression was tested with the data from this study.